Manipulation of the optical properties of colloidal 2D CdSe nanoplatelets - Zhang, Zitong (2023)
Driven by the unique optoelectronic features arising from the strong quantum confinement along the thickness direction, rapid development of CdSe-based nanoplatelets (NPL) has accomplished facile bandgap tunability over a broad spectrum via different preparation protocols or various postsynthesis treatments. The anisotropic geometry of NPLs also stimulates the exploitation of selfassembled CdSe NPL superstructures to enhance light extraction efficiency in display technologies and achieves polarized lasing performance or even electrically pumped laser by adjusting the transition dipole orientation. Although several review articles about the general optical properties of CdSe NPLs have been published, none of them focus on the ability of spectral tunability and precise control of orientations in the solid-state phase of CdSe NPLs. Herein, the band structure engineering approaches in the CdSe NPL family are systematically summarized and the optical properties and device performance metrics of these deliberately engineered NPLs are compared. Then, the recent advanced studies of the motivation and assembly methods of geometrically anisotropic CdSe NPL superlattices are discussed. Finally, the current challenges and future outlook on the controlled modification of optical features and the influences of the approaches in the aspect of CdSe NPL–based devices’ performance are highlighted.